Analysis Of The Financial Performance Of Insurance Companies Before And During The Covid-19 Pandemic Based On Early Warning System And Risk-Based Capital - Pepayosa, Emia Rani; Septiyanti, Ratna Septiyanti (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This study aims to provide empirical evidence regarding the comparison of the value of the Early Warning System and Risk-Based Capital in measuring the financial performance of insurance companies before and during the COVID-19 pandemic. The Early Warning System measurement indicator uses the claim expense ratio. Sampling using purposive sampling method and obtained a sample of 18 insurance companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022. The type of data used is secondary data in the form of financial reports collected through the company's official website and the Indonesia Stock Exchange (IDX). The data analysis method uses non-parametric statistics, namely the Wilcoxon Sign Rank Test with the help of SPSS version 27. The results prove that there is a significant increase in the value of the Early Warning System during the pandemic compared to before the Covid-19 pandemic. The Risk-Based Capital value did not experience a significant decrease during the pandemic compared to before the Covid-19 pandemic. In addition, in this study, the Early Warning System is considered more accurate than Risk-Based Capital because it has a smaller standard error.